Representasi Nilai Toleransi Antar Umat Beragama Dalam Film â€œMy Name Is Khanâ€ Karya Karan Johar (Analisis Semiotika Charles Sanders Pierce) - Ariqqa, Ariqqa; Sikumbang, Ahmad Tamrin; Harahap, Suheri (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
This study aims to determine the representation of the value of inter-religious tolerance in the film My Name Is Khan. The method used in this study is a semiotic analysis method that is descriptive. Where in this study using semiotic analysis from Charles Sanders Pierce. The object of this study is every scene that contains the value of tolerance between religious people.The results of this study show that the film "My Name Is Khan" contains the value of inter-religious tolerance in the form of respecting the beliefs of others, as in one scene where Muslims donate to the family of PMK who died. Giving freedom or independence, as in the scene where Rizwan tries to explain to people the understanding that he is not a terrorist. And mutual understanding, as in the scene where Muslims come to Georgia to help Christians affected by the great flood.